The “Way” Toward E-leadership: Some Evidence From the Field - Torre, Teresina; Sarti, Daria (Frontiers in Psychology, 2020)
Recently, leadership literature has faced the challenge of dealing with a growing pervasive diffusion of information and communication technologies that are deeply changing relationships among workers. Consequently, leadership is continuing to develop through the support of these technologies. This emerging phenomenon has been labeled e-leadership, and it has been studied with the objective of understanding which differences it exhibits from traditional leadership. Our research seeks to examine whether enterprises, which use leadership as an important “tool” to manage workers as effectively as possible, are conscious of this evolution, whether their behavior is supportive of the related needs, and how they are organizing themselves to face the problems and opportunities arising in this new context. The present study has involved 15 Italian companies. Through in-depth interviews based on face-to-face meetings using a semi-structured questionnaire with enterprises’ representatives, we explored the extent of these changes. We developed the analysis across two points in time in order to verify if a change was observable with regard to the way these enterprises considered and managed e-leadership. It was also possible to enhance the role of the technologies themselves in leadership, which in the same period has seen a rapid evolution toward mobile and social developments. Our results help to illuminate that, on the one hand, awareness with regard to e-leadership has increased and, on the other hand, the pervasiveness of technologies is playing a relevant role in the change of leadership together with renewed attention toward soft competencies. We identify four different typologies of e-leadership, which summarize different ways of conceptualizing it, and indicate their main features. We should add that this topic is becoming extremely relevant because of critical crises organizations are now facing (such as the COVID-19 emergency we are experiencing at the present time) and the urgency of adopting e-instruments, which seem now to be the main path to managing the present situation and the aftermath it inevitably will have. Despite this research being carried out before such an event has happened, we believe that its results may further enrich the current lively debate.